grong-Grong تدريس المفردات باستخدام وسيلة جهاز التسجيل فى المدرسة الثانوية الاسلامية الحكومية - Athaillah bin Junaidy; Destantri Mutia Arini (JURNAL AL-IHDA : Media Ilmiah Bahasa Arab, 2021)
The purpose of this study was to determine how the mufradat learning process using recording media and to find out how effective the mufradat learning was using a recording device at Mtsn Grong-grong. This study used an experimental research method with a control class and experimental class design. The collection method was carried out by observation, tests (free test, post test) and documentation. The results of the study showed that mufradat learning using recording media was carried out in five meetings and was effective in improving the learning outcomes of Mtsn Grong-grong students, where the t-count value of 2.365 was greater than the t-table value of 2.03. This means that there is a significant effect of the application of the recording device media in mufradat learning at Mtsn Grong-grong.